Methodology for heat flux investigation on leading edges using infrared thermography. (11th October 2016) - Corre, Y.; Gardarein, J.-L.; Dejarnac, R.; Gaspar, J.; Gunn, J.P.; Aumeunier, M.-H.; Courtois, X.; Missirlian, M.; Rigollet, F.
Abstract: During steady state plasma operation in fusion devices, leading edges of the actively cooled plasma-facing components can be impacted by plasma flux with nearly normal angle of incidence, causing local overheating. The overheating can be a critical issue in high-power machines, especially in the presence of mechanical misalignments. Due to heat diffusion through the material, the edge power overload also leads to a local increase of temperature on the top part of the tile that can be detected by the infrared imaging system (viewed from the top of the machine). In the Tore Supra tokamak, heat flux impinging on the top and the leading edge of the carbon fibre composite (CFC) flat tiles are characterized with both an infrared (IR) thermographic system and 2D thermal modelling of the tile. A specific sensor correction based on a laboratory blackbody-slit experiment has been developed to simulate the spatial resolution related effects (necessary here since the temperature gradient near the leading edge is smaller than the pixel size of the IR system). The transfer function of the IR system is characterized by a Gaussian distribution function. The standard deviation is found to be σ   =  1.75 mm for a pixel size of 3.1 mm. The heat flux calculation is applied to CFC flat tiles and, after being processed with the transfer function, compared to experimental IR data for two geometrical situations: one with 0.2 mm misalignment between two adjacent tiles and the other without misalignment (well-aligned tiles). The heat flux ratio between the leading edge and top is found to be ~25 in the case of the protruding tile, which is lower than the expected ratio using the guiding-centre ballistic approximation with no cross-field heat flux (57).